Harry Potter : 20th anniversary. Return to hogwarts. [videorecording (Blu-Ray)] - Radcliffe, Daniel, 1989-; Grint, Rupert, 1988-; Watson, Emma, 1990-; Columbus, Chris (SDS : Warner Bros. Entertainment, 2022)
Daniel Radcliffe, Rupert Grint, and Emma Watson join filmmaker Chris Columbus and other esteemed cast members across all eight Harry Potter films as they travel back to Hogwarts for the first time to celebrate the anniversary of the franchise's first film, Harry Potter and the Sorcerer's Stone, which premiered twenty years ago. The retrospective special will tell an enchanting making-of story through all-new in-depth interviews and cast conversations, inviting fans on a magical first-person journey through one of the most beloved film franchises of all time. Enjoy!